SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN MOTOR BEKAS TERBAIK MENGGUNAKAN METODE TOPSIS DI SAMPIT - Depi Rusda; raflii (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2023)
Transportation is an isolation movement in the form of an object or person from one place to another. Choosing between several alternatives is a form of systematic decision making to determine a decision from several existing options. The desire for transportation is an absolute in modern life. Transportation facilities, especially non-public transportation capabilities, are needed by the community to transport various necessities of life every day. One of the means of land transportation that is most widely used by people in Indonesia is the motorcycle, because apart from being more economical compared to four-wheeled vehicles, motorbikes have the advantage of being able to reach their destination more quickly. Buying a new motorbike requires a lot of money, and for the lower class, they tend to turn their attention to used motorbikes. However, buying a used motorcycle also confronts them with the problem of what brand and type of motorbike to buy.